Tackling Gendered Violence: Social Workers Intervention in Violence That is Meted Against Men? A Case Study of a Rural Town in a South Africa - Kasa, Luvo (Research in Social Sciences and Technology, 2025)
The study discusses the issue of gendered violence against men and whether laws and legislation equally protect them. It focuses on the findings of research conducted in Bityi, outside Mthatha, which aimed to improve social work interventions in dealing with gender-based violence cases regardless of client gender. It summarises the literature on violence against men and how the concept of Gender-Based Violence (GBV) against men worked in practice. The study also offers a reflection on men's experiences with violence and the need for improved social work intervention. The research was conducted with 12 selected participants using snowball sampling and qualitative methods, and findings were gathered through semi-structured interviews and analysed using thematic content analysis. The study found that men are also victims of gendered violence and further recommended that social workers should be at the forefront of speaking against all forms of violence.